Oscillation Criteria For Even Order Nonlinear Neutral Differential Equations With Mixed Arguments - Thandapani, E.; Padmavathi, S.; Pinelas, Sandra (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
This paper deals with the oscillation criteria for nth order nonlinear neutral mixed type dierential equations.